A Meta-analysis of Vitamin K Status and Cardiovascular Disease (OR33-01-19). (13th June 2019) - Shea, M Kyla; Weiner, Daniel; Matuszek, Gregory; Booth, Sarah; Barger, Kathryn
Abstract: Objectives: Evidence suggests low vitamin K status may be associated with an increased cardiovascular disease (CVD) risk in people with CVD risk factors. The objective of this study was to summarize the association between vitamin K status and CVD, overall and according to baseline CVD risk, by conducting a participant-level meta-analysis using data from the Framingham Offspring Study, the Health, Aging, and Body Composition Study (Health ABC), and the Multi-ethnic Study of Atherosclerosis (MESA). Methods: Circulating phylloquinone (vitamin K1), measured from baseline fasting blood samples, was categorized as ≤0.5 nM, >0.5 - ≤1.0 nM and >1.0 nM. CVD was defined as confirmed ischemic heart disease, angina, resuscitated cardiac arrest, fatal or non-fatal myocardial infarction or stroke. Multivariable Cox proportional hazards models were used to evaluate the association between circulating phylloquinone and incident CVD overall and stratified according to baseline CVD risk factors. Results: Among the 3622 participants (mean (SD) baseline age 65 (11), 45% men, 65% white), there were 785 CVD events over a median of 13.0 years. Overall the risk for CVD did not differ significantly according to circulating phylloquinone categories [HR(95%CI) for CVD, compared to plasma phylloquinone >1.0 nM: ≤0.5 nM = 1.15 (0.96–1.38); >0.5 - ≤1.0 nM = 0.99 (0.84–1.18)]. However, lower circulating phylloquinone was associated with higher incident CVD risk in those with diabetes, with a normal BMI, and in women (Table ). Conclusions: Overall, we did not detect any significant differences in CVD risk across circulating phylloquinone categories in community-dwelling adults. However, low circulating phylloquinone was associated with a higher CVD risk among certain sub-groups, but additional studies are needed to clarify if improving vitamin K status will benefit the cardiovascular health of certain segments of the population. Funding Sources: Supported by NHLBI R21HL133421 and the USDA ARS Cooperative Agreement (58‐1950‐7‐707). Supporting Tables, Images and/or Graphs: